COMPARISON OF THE ADAPTABILITY OF TWO FISSURE SEALANTS IN VARIOUS TOOTH FISSURE MORPHOLOGY PATTERNS: AN IN VITRO EXPERIMENTAL STUDY - Khan, Tabinda Nawaz; Khan, Farhan Raza; Rizwan, Sadia; Khan, Khush Bakht Nawaz; Iqbal, Syeda Noureen; Abidi, Yawar Ali (Journal of Ayub Medical College Abbottabad, 2019)
Background: This study was conducted to compare the adaptation of resin-based sealants with that of Resin modified glass ionome-based sealants in various tooth fissure morphologies. Methods: It was an in vitro experimental study done at the Dow University and NED University, Karachi, Pakistan. Ten extracted human molars were randomly assigned to two groups, (n=5) each. Fissure sealant material (Resin based sealant or resin modified glass ionomer-based sealant) was applied on the occlusal surface of the tooth according to manufacturer's recommendations. Specimens were thermocycled and then sectioned into three longitudinal parts in the bucco-lingual direction. Specimens were examined using scanning electron microscope for the adaptation of the sealant in the occlusal fissure. Mann-Whitney -U test and Kruskall-Wallis test were applied to compare the adaptability scores of sealant materials in the tooth fissure. Level of significance was kept at 0.05.Results: There were no significant differences in the adaptability scores among U-shaped (p-value=0.35), V-shaped (p-value=0.89), IK-shaped (p-value=0.52), I-shaped (p-value-=0.41) and Y-shaped (p-value=1.00) fissure patterns. Similarly, there were no significant differences observed between the resin-based sealant (p-value=0.95) versus RMGIC based sealant (p-value=0.63) for the adaptability scores in various tooth fissure morphologies. Conclusions: No significant difference was found between resin-based sealants and resin modified glass ionomer-based sealants for the adaptation in various tooth fissure patterns. Keywords: Fissure morphology; fissure sealants; RMGIC; flowable resin; scanning electron microscopy